2022
DOI: 10.3389/fneur.2022.922199
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter volume of cerebellum associated with idiopathic normal pressure hydrocephalus: A cross-sectional analysis

Abstract: The cause of idiopathic normal pressure hydrocephalus's (iNPH) clinical symptoms remains unclear. The cerebral cortex is the center of the brain and provides a structural basis for complex perception and motor function. This study aimed to explore the relationship between changes in cerebral cortex volume and clinical symptoms in patients with iNPH. This study included 21 iNPH patients and 20 normal aging (NA) controls. Voxel-based morphometry statistical results showed that, compared with NA, the gray matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…However, this is not the case for the caudate, which instead showed no directional trends. Our results of non-significant differences in caudate volumes are surprising given that changes in basal ganglia structural volumes have been rather consistently reported in NPH studies ( DeVito et al, 2007 ; Ishii et al, 2008 ; Peterson et al, 2019 ; Lv et al, 2022 ) and increases in caudate rCBF were correlated only with patients who showed improvements in apathy post-operatively ( Kanemoto et al, 2019 ). We suggest two alternative hypotheses for this finding.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…However, this is not the case for the caudate, which instead showed no directional trends. Our results of non-significant differences in caudate volumes are surprising given that changes in basal ganglia structural volumes have been rather consistently reported in NPH studies ( DeVito et al, 2007 ; Ishii et al, 2008 ; Peterson et al, 2019 ; Lv et al, 2022 ) and increases in caudate rCBF were correlated only with patients who showed improvements in apathy post-operatively ( Kanemoto et al, 2019 ). We suggest two alternative hypotheses for this finding.…”
Section: Discussioncontrasting
confidence: 59%
“…They also found significantly reduced thalamic, caudate head and periventricular gray matter volumes using voxel-based morphometry (VBM). Using VBM, Lv et al (2022) recently confirmed the presence of both patterns of structural volumetric changes, with decreased gray matter volumes of iNPH in bilateral temporal lobes, bilateral hippocampi, bilateral thalami, bilateral insulae, left amygdala, right lenticular nucleus, right putamen and cerebella and increased gray matter volumes in the bilateral paracentral lobules, precuneus, bilateral supplementary motor areas, medial side of the left cerebral hemisphere, median cingulate and paracingulate gyri. It was also possible using meticulous neuropsychological testing and FSL-based segmentation to show volumetric data could be correlated to neuropsychological scores ( Peterson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 81%
“…Contrarily, it was increased in medial and parietal regions. Global reduction in WM volumes and increase in CSF volumes were also found ( 52 ).…”
Section: Normal Pressure Hydrocephalusmentioning
confidence: 98%
“…But GM degradation had not been detailed in NPH until recently. Lv et al ( 52 ) compared definite NPH patients with controls using MRI scans and found regional variations in GM volume that were significantly different in the NPH group. GM volume was lowered in specific temporal areas, thalamus, hippocampus, and the cerebellum.…”
Section: Normal Pressure Hydrocephalusmentioning
confidence: 99%
“…Magnetic imaging studies have shown that NPH is associated with a decrease in grey matter in some brain areas and increase in others and in particular the cerebellum was adversely affected [ 137 ]. MRI analysis (cine-PC) has been used to evaluate CSF and brain recovery, including tissue stiffness, over 15 months after shunting [ 138 ].…”
Section: Neurological Disordersmentioning
confidence: 99%